Pengaruh Tampilan Website dan Kemudahan Pengguna terhadap Repurchase Intention dengan Customer Satisfaction sebagai Variabel Intervening : Studi Kasus Pada Ecommerce Tokopedia di Yogyakarta - Welsa, Henny; Kusuma Ningrum, Nonik; Saputri, Sella (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine how much influence Website Appearance and Ease Of Use have on Repuchase Intention through Customer Satisfaction as Intervening Variables (Study on Tokopedia E-commerce in Yogyakarta City). The population used in this study were consumers who had shopped at least twice at Tokopedia. The sample in this study was 100 respondents using a quantitative approach, with purposive sampling technique. This data was taken using a questionnaire via the Google form, after the questionnaire results were collected, the data was tabulated using MS Excel and analyzed using multiple linear regression analysis using SPSS version 25. The results of this study indicate that Website Appearance has a positive and significant effect on Customer Satisfaction. Ease Of Use has no effect on Customer Satisfaction. Website Appearance has no effect on Repurchase Intentions. Ease Of Use has a positive and significant effect on Repurchase Intentions. Customer Satisfaction has a positive and significant effect on Repurchase Intentions. Effect of Website Appearance on Repurchase Intention through Customer Satisfaction as an accepted intervening variable. The effect of Ease Of Use on Repurchase Intention through Customer Satisfaction as an intervening variable is rejected.